THE АRCTIC INNOVATIVE CENTER АS A RESOURCE FOR INNOVATIVE DEVELOPMENT OF UNIVERSITY INFRASTRUCTURE - Roman R. Nogovitsyn; Afanasiy A. Vinokurov (Moscow Polytechnic University, 2016)
The article is devoted to the creation and development of innovative infrastructure of university. The coordinating function of the research and education complex is accomplished by the Arctic innovative center. The article focuses on the goals, the key areas of its activity, describes the main achievements of the research laboratories and the activities of small innovation enterprises.